2016
DOI: 10.5937/ffr1601043p
|View full text |Cite
|
Sign up to set email alerts
|

Influence of herbal drugs in broiler chicken nutrition on primal carcass cuts quality assessments

Abstract: Aim of this investigation was to determine the effects of herbal drugs such as garlic, black pepper and hot red pepper in broiler chicken nutrition on carcass primal cuts quality. Total of 1200 one-day old Hubbard broilers were totally randomly distributed into eight dietary treatments with four replicates each. Chicks were fed with three dietary mixtures: starter, grower and finisher. Dietary mixtures in the experiments were as follows: T1 (Control diet), T2 (Garlic powder 0.5 g/100g), T3 (Garlic powder 1.0 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
(7 reference statements)
2
8
0
Order By: Relevance
“…Rabbits fed diets supplemented with hot pepper showed improvement in Feed/Gain ratio, which may be due to its stimulation, carminative, digestion, and antimicrobial properties [21]. Our findings agree with other scientific discoveries of Puvača et al [1], who reported that supplementation of RHP could boost feed utilization by extending the small intestine surface area [21]. The improvement in the hot carcass weight and dressing % results from the reduction in the alimentary tract percentage, which may be due to the addition of RHP.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Rabbits fed diets supplemented with hot pepper showed improvement in Feed/Gain ratio, which may be due to its stimulation, carminative, digestion, and antimicrobial properties [21]. Our findings agree with other scientific discoveries of Puvača et al [1], who reported that supplementation of RHP could boost feed utilization by extending the small intestine surface area [21]. The improvement in the hot carcass weight and dressing % results from the reduction in the alimentary tract percentage, which may be due to the addition of RHP.…”
Section: Discussionsupporting
confidence: 91%
“…The positive effect of hot pepper has been reported in previous studies [3]. Additionally, capsaicin has been reported to stimulate pancreatic, intestinal activities, and increase bile acid secretion [22] and increase BWG in broiler chickens [1]. Carcass results could explain the role of active components in RHP.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Results of Dressing % showed that ranged between 74 to 73.4 %, in group Ag Nanoparticles with Cotula Cineriea extract and group Ag Nanoparticles respectively, but these differences were not significant. Ali et al,2011;Riyazi, (2015;Tabari et al,2016;Bonsu et al, 2012;) Essential oils or their components were not significantly (P>0.05) on Carcass characteristics , on the other hand (Sharma et al,2009;Waskar et al,2011;Oleforuh et al,2015;Puvaca et al,2016) essential oils or their components were not significantly (P>0.05) on Carcass characteristics…”
Section: Dressing %mentioning
confidence: 97%